Accuracy of refractive error measurements in children with strabismus comparing cycloplegic autorefractometry to dry monocular Mohindra retinoscopy - Anna Przekoracka-Krawczyk; Alicja Brenk-Krakowska; Monika Wojtczak-Kwaśniewska (PLoS ONE, 2025)
Objective Uncorrected or undercorrected refractive errors affect 153 million individuals globally, leading to vision impairment and associated quality of life issues. Accurate measurement of refractive errors in children especially with strabismus is critical for effective management. This study evaluates the agreement between near retinoscopy (Mohindra retinoscopy) and cycloplegic autorefractometry in measuring refractive errors among children diagnosed with strabismus. Methods Forty-three strabismic children (18 males, 25 females; ages 3–10 years; mean age 5.5 yo) underwent refractive error evaluations using both methods: Mohindra retinoscopy and cycloplegic autorefractometry. The study assessed spherical component, spherical equivalent, cylinder power, and cylinder vectors J0 and J45. Statistical analyses, including Wilcoxon test Student’s t-test, Bland-Altman analysis, Intraclass Correlation Coefficient (ICC) analysis and correlations (supplementary analysis) evaluated differences, correlations and agreement between the two methods. Results The median spherical component of refractive error was almost equal for both methods used (+4.38 D vs. + 4.50, for Mohindra retinoscopy and cycloplegic autorefractometry, respectively; P = .54), as well as median spherical refractive equivalent (+4.25 for both methods; P = .29). Mean spherical components of refractive errors were nearly identical across both methods, showing Mohindra retinoscopy provided slightly higher hyperopic measurements (0.03 D more positive), whereas spherical equivalent of refractive error showed 0.07 D more positive results for Mohindra retinoscopy than cycloplegic autorefractometry. Median cylinder powers were the same for both methods (-0.50 D; P = .25). No differences were also found for J0 (P = .91) and J45 vectors (P = .88) between Mohindra retinoscopy and cycloplegic autorefractometry. Conclusions Near retinoscopy demonstrates comparable accuracy to cycloplegic autorefractometry in children with strabismus. These findings suggest that Mohindra retinoscopy may be used effectively without the need for cycloplegic intervention during follow-up visits, though further research is warranted to confirm its applicability.